Exploring folklore herbal knowledge: a compilation from Palakkad district, Kerala, India: Exploring folklore herbal knowledge from Palakkad district - Puthanpura Sasidharan, Sreeja; Viji, Zereena; Palakkal Sankaran, Rekha; Muraleedharan, Swathi; K, Jasseera; R, Princy; S, Bhadra; S, Shalom; S, Sunitha; P, Akshatha; S, Anusree; K, Praveena; et al. (Ethnobotany Research and Applications, 2024)
Background: In India, traditional medicine is frequently employed to treat a wide range of illnesses. One such practice that persists in many areas of Kerala is folk medicine. This study aims to document the plants and administration methods used for treating diseases in the folk medicine of various taluks in Palakkad district, Kerala, India. Methods: Data collection involved conducting surveys among villagers in Chittur, Alathur, and Palakkad taluks through regular field visits from January 2022 to March 2023. Twenty informants, aged between 28 and 67 years, were interviewed (Photoplate 1) using pre-structured user-friendly questionnaire. Botanical and common names of plants, plant parts used, and modes of delivery for treatment were documented. Plants reported in the survey other than commercially available in the market were collected and authenticated using floras, and voucher specimens were deposited in the NSS College Herbarium, Nemmara, Palakkad, India. The Use Value (UV) of each therapeutic plant was calculated. Results: The study reported 88 plant species belonging to 45 plant families. Aloe vera (L.) Burm.f. (0.60 UV), Ocimum tenuiflorum L., (0.50 UV) and Zingiber officinale Roscoe (0.50 UV) were the plants with high use value. Most plants were used individually in treatments, whereas 50 remedies were found using combination of different plant species. Common plant families cited in the study included Fabaceae, Lamiaceae, Acanthaceae, Solanaceae, etc. The most frequently used plant part to treat various diseases was the leaf, followed by seeds and rhizome. Conclusion: Our findings contribute to documenting the folklore medicine with detailed formulations, preparation methods, dosage and administration mode that are prevalent in various villages of Palakkad district for a variety of diseases, which would be lost from people’s knowledge. Further, more research on these plants could lead to develop one or more medication candidates. Keywords: Folklore medicine, Zingiber officinale Roscoe, use value, Palakkad